HER2 amplification level by in situ hybridization predicts survival outcome in advanced HER2-positive breast cancer treated with pertuzumab, trastuzumab, and docetaxel regardless of HER2 IHC results - Jeongmin Seo; Jiwon Koh; Dae-Won Lee; Jinyong Kim; Han Suk Ryu; Kyung-Hun Lee; Tae-Yong Kim; Seock-Ah Im (Breast Cancer Research, 2023)
Abstract Background The role of HER2 amplification level in predicting the effectiveness of HER2-directed therapies has been established. However, its association with survival outcomes in advanced HER2-positive breast cancer treated with dual HER2-blockade remains unexplored. Methods This is a single-center retrospective study of patients with advanced HER2-positive breast cancer treated with first-line pertuzumab, trastuzumab, and docetaxel. The primary objective was to ascertain the relationship between treatment outcomes and the level of HER2 amplification by in situ hybridization (ISH). Results A total of 152 patients were included with a median follow-up duration of 50.0 months. Among the 78 patients who received ISH, a higher HER2/CEP17 ratio correlated significantly with longer PFS (HR 0.50, p = 0.022) and OS (HR 0.28, p = 0.014) when dichotomized by the median. A higher HER2 copy number also correlated significantly with better PFS (HR 0.35, p < 0.001) and OS (HR 0.27, p = 0.009). In multivariate analysis, the HER2/CEP17 ratio was an independent predictive factor for PFS (HR 0.66, p = 0.004) and potentially for OS (HR 0.64, p = 0.054), along with HER2 copy number (PFS HR 0.85, p = 0.004; OS HR 0.84, p = 0.049). Furthermore, the correlation between HER2 amplification level by ISH with PFS and OS was consistent across the HER2 IHC 1+/2+ and 3+ categories. Conclusions This is the first study to report that a higher level of HER2 amplification by ISH is associated with improved PFS and OS in advanced HER2-positive breast cancer treated with dual HER2-blockade. Notably, HER2 amplification level had a predictive role regardless of IHC results. Even in patients with HER2 protein expression of 3+, treatment outcome to HER2-directed therapy was dependent on the level of HER2 gene amplification.